Periodontal status in the Down's syndrome subjects living in central‐eastern Italy: the effects of place of living. Issue 3 (21st November 2013) - Zizzi, A; Piemontese, M; Gesuita, R; Nori, A; Berlin, RS; Rocchetti, R; Carle, F; Rubini, C; Aspriello, SD
Abstract Aim The purpose of this study was to determine the influence of the place of living on periodontal status of 62 Down's syndrome (DS) subjects resident at home (DSH) or in specialized institutes (DSI) in central‐eastern Italy. Methods The demographic characteristics of the subjects and the periodontal variables were evaluated according to their living conditions. Descriptive analyses were conducted by stratifying subjects into three age groups (0–13; 14–22; >23 years), using medians and 25th–75th percentiles to summarized data. Comparisons between DSH and DSI subjects were performed using Wilcoxon rank sum test. The effect of demographic and clinical variables on periodontal status was evaluated by means of quantile regression analysis. Results No significant differences resulted between DSH and DSI patients, when compared for gender, age and mental retardation. No significant differences were found in the periodontal variables for the subjects with 0–13 years, while DSI subjects between 14 and 22 years of age presented higher levels of plaque index, probing depth, clinical attachment loss and a lower number of surviving teeth compared to DSH subjects. When DSI and DSH groups ≥23 years of age were compared, no differences were observed in the periodontal conditions except for PI and the number of surviving teeth. Age, body mass index and severe mental retardation were found to be significant predictors of periodontal conditions. Conclusions Institutionalization has a negative effect on surviving teeth number of Down's syndrome subjects. Furthermore, the home care seems to produce benefits on the periodontal conditions of DSH 14–22 years of age.